ADOPTION OF ESG PRACTICES IN PROJECT MANAGEMENT WITH A FOCUS ON IMPLEMENTING EDGE CERTIFICATION (Editora Impacto Científico, 2025)
The construction industry is one of the sectors with the greatest environmental impact. This reality has led companies in the sector to adopt more sustainable practices, seeking to reduce their environmental impact and meet new market demands. Given the above, this study, conducted in Brazil in 2025, analyzed how EDGE certification can be implemented in construction project management to promote sustainability. The research sought to answer the question of how to integrate EDGE certification into project management processes in the Brazilian construction industry and what the main obstacles to its adoption are. The initial hypothesis was that EDGE certification would bring significant economic, social, and environmental benefits. The overall objective of the research was to apply project management to the implementation process for obtaining EDGE certification. The specific objectives were: to assess the economic impacts of adopting EDGE certification and to present the results of EDGE-certified projects and their cost-effectiveness, through sustainable technical solutions. The research used a qualitative and descriptive approach, with data collection based on case studies and comparative analyses, comprising exploratory research. The results indicated that EDGE certification significantly reduces energy and water consumption, as well as CO2 emissions and waste generation. The conclusion is that EDGE certification is an effective tool for promoting sustainability in the Brazilian construction industry, transforming organizational culture and providing significant competitive advantages.DOI: https://doi.org/10.56238/edimpacto2025.089-002